HUMAN RESOURCE MANAGEMENT COUNSELING IN IMPROVING PERFORMANCE AT BUMI PERSADA UNIVERSITY - Azhari; Ayu Anora; Rahmiatul Aula; Raudhatinur; Almunadiya; Sakinah (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2025)
This community service project is titled "Human Resource Management Counseling to Improve Performance at Bumi Persada University." The purpose of this community service is to provide guidance and counseling to lecturers and staff regarding the elements of human resource management. This counseling aims to enhance their insight and knowledge. The implementation method for this community service project is carried out through several activities: the survey stage, where socialization is carried out by preparing various points to be presented during the community service activity, including: preparing the material to be presented, developing a schedule for the presentation, and conducting a site survey. The socialization stage, where a meeting with Bumi Persada University officials is conducted prior to the community service activity to convey the intent and purpose of the community service. This stage also establishes collaborations and determines the community service schedule. The community service implementation team consists of four lecturers from the Faculty of Economics and Business, Management Study Program. The community service team provides material on Human Resource Management, Management, the Definition of Human Resource Management, Reward Systems, Educational Quality, and Performance.